Leadership for social justice and democracy in our schools - Blankstein, Alan M. 1959-; Houston, Paul D. (Soul of educational leadership, 2016)
This ninth and final book in 'The Soul of Educational Leadership' series offers practical strategies for promoting socially responsible school cultures that enhance student engagement